MERAMU KETENTUAN HUKUM ISLAM TERKAIT KHITAN PEREMPUAN - Fadhli, Ashabul (JURIS (Jurnal Ilmiah Syariah), 2015)
Observing several academic documents that enrich the historical value, the discourse about circumcision apparently still presents interesting questions and ideas according to the conditions and social culture surrounding them. Cutting a small portion of the genitals on the implementation of circumcision is commonly done throughout the community on the child's age. The social values that legitimize female circumcision should be criticized because it may cause bad impact. Meanwhile, according to religious dogma, female circumcision is not a significant issue. Therefore, the practice of circumcision continues to be executed, but some of them lead to contradictory disagreement. Kata kunci: khitan, perempuan, hukum Islam